Screening for phenotypic and genotypic resistance to antibiotics in Gram positive pathogens - FARKAS, Anca; TARCO, Emma; CRĂCIUNAŞ, Cornelia; BOCOŞ, Brînduşa; BUTIUC-KEUL, Anca-Livia (Studia Universitatis Babeș-Bolyai Biologia, 2017)
Gram positive bacteria such as methicillin resistant Staphylococcus aureus, vancomycin resistant enterococci or multidrug resistant Streptococcus spp. are increasingly involved in severe infections with serious clinical consequences. The aim of this study is to investigate phenotypic and genotypic resistance traits in Gram positive pathogens isolated from clinical specimens in Cluj-Napoca, Romania. A total number of 31 Enterococcus spp., Staphylococcus spp. and Streptococcus spp. strains were subjected to antimicrobial susceptibility testing by disc diffusion, while the carriage of 26 antibiotic resistance genes and of class 1 integron was assessed by PCR. Bacterial pathogens included in this study were mostly susceptible to folate pathway inhibitors (100%), oxazolidinones (97%), fosfomycins (93%) and glycopeptides (92%). Enterococci, staphylococci and streptococci displayed high levels of phenotypic resistance to penicillins, tetracyclines and macrolides, a percentage of 42% being multidrug resistant. The strains under this study proved to be able to produce β-lactamase enzymes encoded by the TEM-1 gene and aminoglycoside modifying enzymes due to the carriage of aac(6’)-Ie-aph(2”) gene, to possess ribosomal protection mechanisms for macrolide and tetracycline resistance associated with ermB, ermC and tet(M) genes and to bear efflux genes tet(A), tet(B), tet(C) ant tet(L). Class 1 integron integrase was detected in 16% of the isolates, but no significant correlations were found between the carriage of intI1 gene and the phenotypic or genotypic resistance among the Gram positive pathogens investigated.